2015
DOI: 10.4049/jimmunol.1301850
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Enhances FcεRI-Mediated Cytokine Production by Mast Cells through Direct and Indirect Mechanisms

Abstract: Th2-type cytokines and TNF-α secreted by activated mast cells upon cross-linking of FcεRI contribute to the development and maintenance of Th2 immunity to parasites and allergens. We have previously shown that cytokine secretion by mouse mast cells is enhanced by signaling through Notch receptors. In this study, we investigated the molecular mechanisms by which Notch signaling enhances mast cell cytokine production induced by FcεRI cross-linking. FcεRI-mediated production of cytokines, particularly IL-4, was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…To determine the effect of Resveratrol on downstream signaling processes, we analyzed the phosphorylation status of Akt, p38 and p42/44 (ERK1/2) following FcεRI cross-linking since these intermediate signaling molecules have been implicated in activation of various transcription factors and cytokine production by mast cells [17,35,36]. To do so, SDS-PAGE and Western blotting were performed using whole cell lysates prepared from IgE-sensitized human skin mast cells that were pre-treated with Resveratrol at 1, 10 or 100 µM for 1 h, and challenged for 5 min with 100 ng/ml NP-BSA.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of Resveratrol on downstream signaling processes, we analyzed the phosphorylation status of Akt, p38 and p42/44 (ERK1/2) following FcεRI cross-linking since these intermediate signaling molecules have been implicated in activation of various transcription factors and cytokine production by mast cells [17,35,36]. To do so, SDS-PAGE and Western blotting were performed using whole cell lysates prepared from IgE-sensitized human skin mast cells that were pre-treated with Resveratrol at 1, 10 or 100 µM for 1 h, and challenged for 5 min with 100 ng/ml NP-BSA.…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown of the Notch2 gene was performed with lentiviral vectors pLKO.1-puro expressing a short hairpin RNA (shRNA) targeting mouse Notch2 (TRCN0000340451) [31], which were purchased from MISSION shRNA Library (Sigma Aldrich Co. LLC.).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we previously reported that Notch signaling enhances FcεRI-mediated T H 2 cytokine production. 15 These data suggest that immature mast cells undergo a phenotypic change toward mature MMCs by means of Notch signaling. Thus inhibition of Notch signaling is anticipated to alleviate some symptoms associated with food allergy that are caused by activated MMCs.…”
Section: Inhibition Of Notch Signaling Alleviates Symptoms Associatedmentioning
confidence: 84%
“…12 Previous reports have shown that Notch1 and Notch2 are constitutively expressed on mouse mast cells, and Notch signaling induces MHC class II expression on mast cell surfaces and enhances FcεRI-mediated cytokine production by mast cells. [13][14][15] However, the mechanism by which Notch signaling regulates MMC distribution in the intestine remains unclear.…”
mentioning
confidence: 99%